Recent advances in edible seaweeds: Ingredients of functional food products, potential applications, and food safety challenges - Ali, Muhammad Qasim; Mohd Akmal, Azhar; Mimi Sakinah, Abdul Munaim; Nur Fathin, Ruslan; Noormazlinah, Ahmad; Noman, Abeer Essam (Springer Nature, 2025)
Edible seaweeds are increasingly recognized for their potential as functional food products due to their rich nutritional profile and bioactive compounds. Seaweeds offer various uses, ranging from direct consumption as food to the synthesis of industrial food products, mostly agar and alginate. The numerous benefits of seaweeds include their rich content of minerals, vitamins, phenols, polysaccharides, and other active compounds. Extraction techniques for edible seaweeds are also discussed in this review, including microwave-assisted extraction, pulsed electric field-assisted extraction, supercritical fluid extraction, and ultrasound-assisted extraction. The prospective applications of seaweeds in the food industry are vast, ranging from their use as natural additives and preservatives to their incorporation in innovative food products to improve nutritional consumption. This review explores seaweed’s functional properties, highlighting its role in enhancing food quality and promoting wellness. This paper aims to provide a holistic overview of the functional food potential of edible seaweeds, their diverse applications, and the food safety issues, such as heavy metal contamination, addressed to ensure their safe consumption.